QUALITY MANAGEMENT OF INFORMATION TECHNOLOGY GOVERNANCE COBIT 2019 FRAMEWORK EDUCATION FACTORS IN INDONESIA: A REVIEW - Prasetya, Bismar Rifki wahyu; Muhammad, Alva Hendi (Universitas Khairun, 2025)
This study examines information technology (IT) governance in Indonesia's education sector using the COBIT 2019 framework through a systematic literature review (SLR) approach. COBIT 2019 is a globally recognized framework designed to help organizations manage IT effectively by integrating quality management principles to achieve strategic objectives. In the education sector, implementing robust IT governance is crucial to supporting ongoing digital transformation efforts. The SLR process involved identifying, selecting, and analyzing relevant literature to assess the implementation of COBIT 2019 in the Indonesian education sector. The findings indicate that this framework can enhance IT governance quality, particularly in risk management, resource efficiency, and operational sustainability. However, challenges persist, including limited managerial understanding, shortages of skilled human resources, and inadequate infrastructure support. To address these challenges, collaboration among the government, educational institutions, and the private sector is essential. Additionally, continuous training programs are necessary to enhance the competencies of management and IT personnel in effectively implementing COBIT 2019. The study underscores the importance of integrating technological and educational aspects to improve service quality in the education sector. Furthermore, the COBIT 2019 framework is recognized as a valuable tool for fostering collaboration among stakeholders to achieve sustainable education development in Indonesia.